2017
DOI: 10.14235/bs.2017.910
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Chronic Diseases and Drug Use Among Geriatric Cases in Ardesen County of Rize Province

Abstract: ÖZAmaç: Bu çalışmanın amacı, Rize ili Ardeşen ilçesindeki geriatrik olgular arasında kronik hastalık sıklığı ve ilaç kullanımlarını değerlendirmektir. Yöntemler: Kesitsel ve tanımlayıcı ilişki arayıcı nitelikteki çalış-ma, Mart-Haziran 2014 tarihleri arasında 482 yaşlı bireyle yapıl-dı. Veriler, yüz yüze görüşme tekniği tekniği kullanılarak Kişisel Bilgi Formu ile toplandı. Veriler, yüzdelik ve Ki kare testi ile değerlendirildi. Bulgular: Bu çalışmada, yaşlıların %52,9'u 65-74 yaş grubunda ve %97,9'u kronik ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Aging may cause numerous physical, cognitive, and social problems for elderly individuals and affect their quality of life [ 2 , 3 ]. Several common age-related diseases include cardiovascular disease, chronic lung disease, diabetes, and constipation due to prolonged physical inactivity [ 4 , 5 ]. Evidence has indicated that approximately 25% of elderly people suffered from constipation, as one of the most common digestive disorders [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging may cause numerous physical, cognitive, and social problems for elderly individuals and affect their quality of life [ 2 , 3 ]. Several common age-related diseases include cardiovascular disease, chronic lung disease, diabetes, and constipation due to prolonged physical inactivity [ 4 , 5 ]. Evidence has indicated that approximately 25% of elderly people suffered from constipation, as one of the most common digestive disorders [ 6 ].…”
Section: Introductionmentioning
confidence: 99%